Serum ferritin levels in human immunodeficiency virus infected children and its relation with severe immunodeficiency - Kumar, Durgesh; Singh, Mukesh Vir; Sharma, Indra Kumar; Kumar, Dinesh; Shukla, Krishan Mohan; Singh, Dhamendra Kumar (International Journal of Contemporary Pediatrics, 2017)
Background: Ferritin is an acute phase protein which is often elevated in acute and chronic inflammation. In adults with human immunodeficiency virus (HIV) infection, elevated serum ferritin levels indicate advanced or progressive disease. In the present study, ferritin levels were evaluated in HIV infected children to find out its relation with the immune deficiency. Methods: The children who were HIV positive (confirmed by ELISA for HIV-1 and HIV-2), and attending the OPD of ART Centre and of tertiary care center during period of one year were included in the study. The study population consisted of 47 patients, belonging to both sexes and age of 18 months to 19 years. Detailed history was taken and full clinical examination done in all cases. Blood sample for Complete blood count, serum ferritin and CD4 count was taken. Absolute CD4 count of each patient was obtained and immunological staging was done on the basis of WHO immunological staging criteria. Serum ferritin level 7-140 ngm/mL was considered normal. Results: Hyperferritenimia (>140 ngm/ mL) is a feature of advanced stages of HIV infection. 11.1% patients of stage 3 and 40.0% patients of stage 4 are showing hyperferritinemia (r = 0.890), irrespective of anemia. Low serum ferritin level (<7 ngm/mL) is an unusual feature in HIV infected children. Conclusions: High Serum ferritin levels are not uncommon in children with HIV disease and they are related with immunological progression of the disease.